Phase 2 study of natalizumab plus standard corticosteroid treatment for high-risk acute graft-versus-host disease - Al Malki, Monzr M.; London, Kaitlyn; Baez, Janna; Akahoshi, Yu; Hogan, William J.; Etra, Aaron; Choe, Hannah; Hexner, Elizabeth; Langston, Amelia; Abhyankar, Sunil; Ponce, Doris M.; DeFilipp, Zachariah; et al. (Blood Advances, 2023)
Graft-versus-host disease (GVHD) of the gastrointestinal (GI) tract is the main cause of nonrelapse mortality (NRM) after allogeneic hematopoietic cell transplantation. Ann Arbor (AA) scores derived from serum biomarkers at onset of GVHD quantify GI crypt damage; AA2/3 scores correlate with resistance to treatment and higher NRM. We conducted a multicenter, phase 2 study using natalizumab, a humanized monoclonal antibody that blocks T-cell trafficking to the GI tract through the α4 subunit of α4β7 integrin, combined with corticosteroids as primary treatment for patients with new onset AA2/3 GVHD. Seventy-five patients who were evaluable were enrolled and treated; 81% received natalizumab within 2 days of starting corticosteroids. Therapy was well tolerated with no treatment emergent adverse events in <10% of patients. Outcomes for patients treated with natalizumab plus corticosteroids were compared with 150 well-matched controls from the MAGIC database whose primary treatment was corticosteroids alone. There were no significant differences in overall or complete response between patients treated with natalizumab plus corticosteroids and those treated with corticosteroids alone (60% vs 58%; P = .67% and 48% vs 48%; P = 1.0, respectively) including relevant subgroups. There were also no significant differences in NRM or overall survival at 12 months in patients treated with natalizumab plus corticosteroids compared with controls treated with corticosteroids.
CRIS-Team Scopus Importer:2023-09-29